Comparison of effectiveness and drug cost between dipeptidyl peptidase‐4 inhibitor and biguanide as the first‐line anti‐hyperglycaemic medication among Japanese working generation with type 2 diabetes. Issue 1 (3rd June 2019) - Ihana‐Sugiyama, Noriko; Sugiyama, Takehiro; Tanaka, Hirokazu; Ueki, Kohjiro; Kobayashi, Yasuki; Ohsugi, Mitsuru
Abstract: Aims and Objectives: Dipeptidyl peptidase‐4 inhibitor (DPP4i) is widely used for the treatment of type 2 diabetes (T2DM) in several countries such as Japan, whereas biguanide (BG; mostly metformin) is recommended as a first‐line antidiabetic medication in many countries according to evidence mainly from Western countries. Although previous studies reported that DPP4i may be more efficacious for East Asians, direct comparisons of effectiveness and cost between DPP4i and BG have never been conducted in East Asia. Methods: We extracted claims and medical check‐up data (observation period from January 2010 to March 2016) of adult patients under 70 years old with T2DM who received DPP4i or BG as first‐line antidiabetic drugs. Changes in HbA1c and BMI before and 2 years after the first prescription and annual cost of antidiabetic medication during the second year were compared between the DPP4i and BG groups. Results: We extracted 1034 patients who received DPP4i and 365 patients who received BG as the first antidiabetic medication (male sex, 83.0% and 84.9%; HbA1c (mean [SD]), 7.7 [1.4]% and 7.9 [1.4]%; BMI, 26.6 [4.5] kg/m 2 and 28.1 [4.3] kg/m 2 ). After propensity score matching, changes in HbA1c and BMI were not significantly different between the groups (HbA1c, −0.67% vs −0.80% [ P  = .28]; BMI, −0.3 kg/m 2 vs −0.4 kg/m 2 [ P  = .42]). Annual cost of antidiabetic drugs was significantly higher in the DPP4i group (US $458.7 vs 273.3 [ P  < .001]). Many patients continued each medication at the follow‐up visit (78.3% of the DPP4i group and 73.7% of the BG groups). Conclusions: The first antidiabetic prescription for the patient was mostly continued thereafter. BG may be recommendable as the first‐line medication for patients with T2DM, especially for middle‐aged, male population with greater BMI. It is worth addressing the discrepancy between practice in Japan and that recommended in international guidelines.